Gestão de recursos humanos e o terceiro setor: um estudo descritivo das organizações de Belo Horizonte - Lilian Bambirra de Assis (2005)
The objective of this dissertation was to describe how the management of human resources in the third sector organizations located in Belo Horizonte occurs. From the importance this sector is assuming in the national scene, some challenges emerge for these institutions, as abigger competition for resources, what increases the need of a more efficient management. The study consisted of a descript-qualitative research where documents and halfstructuralized interviews were used in the 22 organizations that composed the sample. Considering the crisis of the Welfare State as a background and understanding that management practices lead to the necessity of an appropriate management of HR, one understands that the inherent rationality of the organizations, allows to search a theoretical construction that strengthens this mutual bond between the third sector organizations and the management of human resources. In a conclusive way, if in one hand the HR management analysis showed up the lack of relevance that this activity assumes, despite the strong speech of the individual valorization, on the other hand this area presented enough capacity of insertion and agility, without a dependence of the formalization of the activities that weresupposed to be identified. Despite of the speech of the importance at the people valuation, there are some practices that have taken root in what more anachronistic in terms of management concern of people exists, and they cannot and do not have only to be analyzed under this perspective, because its insertion and social relevance is associated with the capacity of taking care of its interested public. But certainly, a minimum of rationalization and professionalism would be in accordance with what literature proclaims, being able to overcome a still little elucidative period in terms of vanguard management.